2505. A Novel Mobile Phone Application for Remote Research Data Collection is Effective in Monitoring Chronic Sequelae After Acute Viral Infections. (26th November 2018) - Teh, Yii Ean; Kalimuddin, Shirin; Ang, Sze Chien; Lee, Natalie Mei Ying; Ooi, Eng Eong; Low, Jenny; Sasisekharan, Ram; Paintal, Shay; Clark, Thomas
Abstract: Background: Although much is known about the presentation of acute viral infections such as dengue fever, the long-term sequelae has not been systematically studied. Anecdotal evidence suggests that many viral infections, particularly flaviviral infections, may have long-term sequelae. Prospective longitudinal studies to evaluate such chronic health outcomes, however, require subjects to comply with multiple follow-up clinic visits, making them costly to run and vulnerable to high dropout rates. Using acute dengue and other febrile illnesses (OFI) as test cases, we aimed to explore the utility of a mobile phone application to evaluate the long-term sequelae and self-reported health outcomes in a cohort of patients up to one year post infection. Methods: We designed a M obile-phone A pplication for I nformation extraction in Den gue (MAIDEN) to study the long-term health outcomes of acute dengue compared with OFI. Demographic and clinical information was collected from the study participants at enrollment. Participants were sent a link via e-mail to download MAIDEN onto their mobile phone. Except for the day 1 visit, participants were not required to attend the study site in-person, but instead used MAIDEN to remotely enter information on symptoms experienced at stipulated intervals. Results: A total of 44 participants have been recruited to date. 4 participants had acute dengue infection and 40 had OFI. The overall study follow-up compliance rate was 89.2%. 23/44 patients have completed visits up till day 21. Of these 23 patients, 43% reported symptoms at day 7 and 39% at day 21. The table below shows the number of individual symptoms experienced by these participants. Conclusion: Chronic symptoms continue to persist in a significant proportion of patients with acute viral illnesses. Mobile applications such as MAIDEN can serve as useful tools to support remote research data collection, making longitudinal follow-up of such patients feasible. Disclosures: All authors: No reported disclosures.